BACTERIAL CORE FLOODING ON LIMESTONE ARTIFICIAL CORE FOR MICROBIAL ENHANCED OIL RECOVERY (MEOR) APPLICATION - Sinta Setyaningrum (Jurusan Teknik Perminyakan Fakultas Teknologi Kebumian dan Energi Universitas Trisakti, 2021)
Microbial Enhanced Oil Recovery (MEOR) is a tertiary methods to increase oil production using bioproduct of microorganisms form acidic compounds, gases, polymers, and surfactants, as an agent that can alter the characteristics of the reservoir rock and oil. Previous laboratory research indicated that bacterial isolates indigen from petroleum reservoir, MSD4 and MSD5, with the amount of inoculum ratio 1:1 in recovery medium can reduce the viscosity value and interfacial tension of oil. The aim of this research was to determine the amount of oil recovery from low saturated oil in limestone artificial core by using bacterial core flooding method, also to determine the physical character and chemical character changes in limestone rocks and petroleum. Each bacteria, MSD4 and MSD5, were adapted to the medium SMSS that have been added by 5% oil. Inoculum of indigen bacterial cultures to be injected into the limestone core was bred in the SMSS culture medium added molasses with a varied amount, as much as 1%, 2%, and 3%. From the those variation, the amount of molasses added as much as 1% in the medium SMSS, is known that MSD4 and MSD5 cultures can grow to the highest μ respectively at the age of 16-hour and 24-hour with a value at 0.9992 hours-1 and 0, 9993 hours-1. Inoculum MSD4 and MSD5 cultures with the amount of 1:1 ratio and each bacterial cell density 107-108 cells/mL, were injected into artificial limestone cores with oil saturated less than 15%. The value of rock porosity range used for the simulation of bacterial flooding is 37% -42%, while permeability range used low permeability value (1mD-10mD) and fair permeability value (10mD-50mD). High oil recovery factor (RF%) were obtained from bacterial flooding simulation and incubated for 7 days in a temperature of 55°C on medium SMSS for cores with low permeability values and fair, has a range of 16,3% - 32% and 12% -15,3%. The result of microorganisms activity in limestone rocks from a change on physical character, have a range at -41,8% - 698% on permeability value and a range at -63,85% - 1,03% on porosity value. Indicator of bacterial attachment on limestone cores can be determined by photomicrographs analyzing Scanning Electron Microscope and Energy Dispersive X-ray Spectroscopy.